Analysis of Internal and External Factors Affecting to Students' Weaknesses in Learning English Speaking Skills - Jihan Althof; M. Hanafi; Mohammad Luqman (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
This study aims to investigate the role of Indonesian in reducing English speaking anxiety in junior high school students. The study was conducted at MTs Negeri 4 Sidoarjo in the 2024/2025 academic year, with a population of all eighth-grade students. The sample was determined purposively by nine students from class 8D representing three participation categories: active, shy, and passive. The instruments used were classroom observation and semi-structured interviews to explore students’ experiences regarding the use of Indonesian during English learning. Data were analyzed thematically through the stages of transcription, coding, categorization, and interpretation. The results showed that Indonesian has different functions for each group of students. Active students use it as a supporting tool to maintain fluency in speaking and increase confidence when having difficulty remembering English vocabulary. Shy students use it as a bridge when forgetting words or being unsure about constructing sentences, so they can remain engaged without withdrawing. Passive students rely heavily on Indonesian as a shield to reduce their fear of mistakes or ridicule, allowing them to participate, albeit with limited proficiency. These findings confirm that Indonesian is not a barrier, but rather a strategic resource that can help reduce anxiety, maintain engagement, and support the gradual improvement of speaking skills. Therefore, teachers are advised to implement a flexible and strategic bilingual approach to create a supportive classroom atmosphere, emphasize participation over perfection, and build students’ confidence in communicating in English.